Transformasi Metodologi Studi Islam dari Pemahaman Tekstual ke Kontekstual Modern - Ittikhatul Mudawamah; Lumngatul Khabibah; Mukmin Mukmin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The transformation of Islamic studies methodology from textual to contextual approaches marks a significant epistemological shift in modern Islamic scholarship. This study aims to explore the dynamics behind this paradigm change, identify the methodological tensions between textual and contextual approaches, and analyze how contemporary challenges shape the development of Islamic interpretation. The research problem centers on the inadequacy of purely literal readings in addressing modern issues such as digital ethics, gender relations, and socio-cultural change, contrasted with concerns that contextual approaches may weaken normative religious foundations. Using a qualitative library research method, this study analyzes scholarly works, classical references, and contemporary academic discourse to map the evolution of Islamic methodological thought. The findings demonstrate that contextual and integrative approaches increasingly complement traditional textual methods by incorporating historical, sociological, and hermeneutical perspectives. These methods provide more relevant and adaptable interpretations for contemporary needs while preserving core Islamic values. The study concludes that methodological renewal is essential for maintaining the relevance of Islamic teachings in modern society and highlights the need for stronger methodological literacy within Islamic education.   Keywords: Islamic methodology, textual approach, contextual interpretation, hermeneutics, paradigm shift